Frame-Based Semantic Representation and Similarity Analysis in Audio Description Scripts - Gamonal, Maucha Andrade; Pagano, Adriana Silvina; Torrent, Tiago Timponi; Matos, Ely Edison (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2025)
We present a semantic similarity analysis between two versions of audio description scripts for a Brazilian short film, based on Frame Semantics and the FrameNet Brasil annotation model. Our study applies manual frame-based semantic annotation, identifying lexical units, frames, and frame elements. A similarity metric combining spread activation and cosine similarity is employed to measure semantic overlap, showing that variations in frame evocation reflect different narrative and descriptive choices across scripts. This work demonstrates how frame-based models can capture semantic overlap and divergence in multimodal translation tasks such as audio description.